2023
DOI: 10.1111/jgs.18492
|View full text |Cite
|
Sign up to set email alerts
|

Associations of sex, Alzheimer's disease and related dementias, and days alive and at home among older Medicare beneficiaries recovering from hip fracture

Abstract: BackgroundMales constitute 25% of older adults who experience hip fractures in the United States; a concerning upward trend given poorer health and outcomes among male survivors. Male sex is associated with worse cognitive performance after hip fracture, impacting participation in rehabilitation and long‐term outcomes especially for those with Alzheimer's disease or related dementias (ADRD). However, little research has evaluated whether sex differences in post‐fracture recovery are greater among those living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Impaired cognition has been significantly associated with high mortality rates, 1 , 2 increased risk of recurrent fractures and prosthetic hip dislocations, 3 , 4 blunted ability to function in activities of daily living, 5 , 6 impaired mobility, 7 low likelihood of discharge home and reduced number of days alive and at home, a combined patient-centered outcome measure. 8 , 9 The recent results are in agreement with a lot of previous original studies and various systematic reviews: on the whole, the wider literature has consistently reported poor outcomes in cognitively impaired subjects with a fragility fracture of the hip. 10 - 12 Notably, the presence of cognitive impairment has been associated with poor outcomes independently of many potential confounders.…”
supporting
confidence: 87%
“…Impaired cognition has been significantly associated with high mortality rates, 1 , 2 increased risk of recurrent fractures and prosthetic hip dislocations, 3 , 4 blunted ability to function in activities of daily living, 5 , 6 impaired mobility, 7 low likelihood of discharge home and reduced number of days alive and at home, a combined patient-centered outcome measure. 8 , 9 The recent results are in agreement with a lot of previous original studies and various systematic reviews: on the whole, the wider literature has consistently reported poor outcomes in cognitively impaired subjects with a fragility fracture of the hip. 10 - 12 Notably, the presence of cognitive impairment has been associated with poor outcomes independently of many potential confounders.…”
supporting
confidence: 87%
“…Consistent with our prior work, home time was calculated by subtracting the number of days spent in an inpatient, skilled nursing facility, nursing home, emergency department observation, or outpatient observation setting (i.e., patient is in the hospital but has not been technically admitted), and the number of days spent deceased, from the total follow‐up available for each of the 12 follow‐up months (monthly level) 33,34 . This definition of home time extends prior work to include emergency department and outpatient observation settings, which are technically not time spent at home 22,35 .…”
Section: Methodsmentioning
confidence: 99%